Prescribed Performance Tracking Control for Nonlinear Stochastic Time-Delay Systems with Multiple Constraints - Man Zhang; Ru Chang; Ying Wang (Actuators)
This paper proposes a prescribed performance tracking control scheme for a category of nonlinear stochastic time-delay systems with input saturation and state asymmetric time-varying constraints. First, to solve the non-differentiable problem caused by input saturation, a smooth nonlinear function was utilized to approximate the saturation function. A nonlinear mapping technique was employed to transform the constrained problem into a bounded convergence problem. The time-delay problem was then solved by constructing the corresponding Lyapunov–Krasovskii function. The error feedback controller was constructed by combining the backstepping technique, the dynamic surface technique, the neural network approximation technique, and the adaptive control method. Based on stochastic mean-square stability theory, all signals in the closed-loop system are proven to be bounded under the designed control scheme. Also, this scheme ensures that the system states always stay within the constraint range, and the tracking error meets the prescribed performance constraint. Finally, the feasibility and superiority of the proposed control scheme were validated through simulation.